White's handbook of chlorination and alternative disinfectants. - White, George Clifford (Wiley, 2010)
"Since the publication of the Fourth Edition of White's Handbook of Chlorination and Alternative Disinfectants more than ten years ago, the water industry has made substantial advances in their understanding and application of chlorine, hypochlorite, and alternative disinfectants for water and wastewater treatment. This Fifth Edition, with its extensive updates and revisions, reflects the current state of the science as well as the latest practices. Authored and reviewed by leading experts in the field of water and wastewater treatment, this Fifth Edition remains an ideal reference for utilities, regulators, engineers, and plant operators who need current information on the disinfection of potable water, wastewater, industrial water, and swimming pools"--Resource description page.